Impact of 10 years of adaptive multi-paddock grazing on soil carbon and beef's greenhouse gas footprint in the US Upper Midwest - Lautaro Garcia; Paige L. Stanley; Joao P. Sacramento; Jasmine A. Dillon; Mariko Thorbecke; Logan R. Thompson; Vrinda Ambike; Prateek Sharma; Sutie Xu; Marilia B. Chiavegato; Matt R. Raven; Bruno Basso; et al. (Agricultural Systems, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Association of prenatal exposure to criteria air pollutants and traffic-related air toxics with adverse birth outcomes: A population-based cohort study in California (1990–2021) - Sanjali Mitra; Karl O'Sharkey; Seung-a Paik; Laura Thompson; Jason Su; Myles Cockburn; Roch A. Nianogo; Beate Ritz (Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Severe fire has impacted populations of the California spotted owl more than fuels management or drought-related tree mortality - Elizabeth Ming-Yue Ng; Connor M. Wood; H. Anu Kramer; Jason M. Winiarski; Kate A. McGinn; Sheila A. Whitmore; Jonathan P. Eiseman; Kevin G. Kelly; Sarah C. Sawyer; Craig Thompson; M. Zachariah Peery (Forest Ecology and Management, 2026)

Fuels management mitigates megafires to the benefit of old forest species - Kate McGinn; Gavin M. Jones; H. Anu Kramer; Sheila A. Whitmore; Jason M. Winiarski; Elizabeth Ming-Yue Ng; Connor M. Wood; Sarah C. Sawyer; Craig Thompson; M. Zachariah Peery (Forest Ecology and Management, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Nutritional attributes, health benefits, consumer perceptions and sustainability impacts of whole pulses and pulse flour-based ingredients - Rie Sadohara; Karen Cichy; Henry Thompson; Mark A. Uebersax; Muhammad Siddiq; Jason Wiesinger (Critical Reviews in Food Science and Nutrition, 2026)

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Military-Related Weight Stigma Prospectively Predicts Dietary Restraint During Pregnancy in US Military Active-Duty Service Members: A Longitudinal Observational Study - Katherine A. Thompson; Viviana Bauman; Ruby Schrag; Marney A. White; Autumn Mains; Stephanie Rioux; Holly Spinner; Isabel Thorstad; Victoria Thomas; David Klein; Mark Haigney; Marian Tanofsky-Kraff; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Decentring our appreciation of the association of factors and cities' mitigation patterns - Sombol Mokhles; Kathryn Davidson; Jason Thompson; Michele Acuto (Urban Climate, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Development and preliminary validation of a modified Food Craving Inventory for Pregnancy (FCI-P) in U.S. military active-duty Service women - Katherine Thompson; Marney A. White; Ruby Schrag; Jason M. Lavender; Viviana Bauman; Autumn Mains; Stephanie Rioux; Holly Spinner; Isabel Thorstad; David Klein; Mark Haigney; Marian Tanofsky-Kraff (Appetite, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Resource overlap and infrequent predation on key pests show vulnerability in cotton biological control services - Jason M. Schmidt; Katherine Russell; Carson Bowers; Alisa W. Coffin; Melissa Thompson; Erin E. Grabarczyk; P. Glynn Tillman; Dawn Olson (Agriculture, Ecosystems & Environment, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

An emerging food policy domain: The effects of autonomous transport technologies on food access and consumption - Simone Pettigrew; Leon Booth; Victoria Farrar; Prof Julie Brown; Branislava Godic; Jason Thompson (Food Policy, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Terrestrial lidar reveals new information about habitats provided by large old trees - Alexander Holland; Philip Gibbons; Jason Thompson; Stanislav Roudavski (Biological Conservation, 2024)

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

A critical re‐analysis of constraints on the timing and rate of Laurentide Ice Sheet recession in the northeastern United States - Christopher T. Halsted; Paul R. Bierman; Jeremy D. Shakun; P. Thompson Davis; Lee B. Corbett; Jason S. Drebber; John C. Ridge (Journal of Quaternary Science, 2024)
We review geochronological data relating to the timing and rate of Laurentide Ice Sheet recession in the northeastern United States and model ice margin movements in a Bayesian framework using compilations of previously published organic 14 C ( n = 133) and in situ cosmogenic 10 Be ( n = 95) ages. We compare the resulting method‐specific chronologies with glacial varve records that serve as independent constraints on the pace of ice recession to: (1) construct a synthesis of deglacial chronology throughout the region; and (2) assess the accuracy of each chronometer for constraining the timing of deglaciation. Near the Last Glacial Maximum terminal moraine zone, 10 Be and organic 14 C ages disagree by thousands of years and limit determination of the initial recession to a date range of 24–20 ka. We infer that 10 Be inherited from pre‐glacial exposure adds 2–6 kyr to many exposure ages near the terminal moraines, whereas macrofossil 14 C ages are typically 4–8 kyr too young due to a substantial lag between ice recession and sufficient organic material accumulation for dating in some basins. Age discrepancies between these chronometers decrease with distance from the terminal moraine, due to less 10 Be inherited from prior exposure and a reduced lag between ice recession and organic material deposition. 14 C and 10 Be ages generally agree at locations more than 200 km distal from the terminal moraines and suggest a mostly continuous history of ice recession throughout the region from 18 to 13 ka with a variable pace best documented by varves.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Corrigendum: Rise of the machines: Best practices and experimental evaluation of computer-assisted dorsal fin image matching systems for bottlenose dolphins - Reny B. Tyson Moore; Kim W. Urian; Jason B. Allen; Carolyn Cush; Jason R. Parham; Drew Blount; Jason Holmberg; Jamie W. Thompson; Randall S. Wells (Frontiers in Marine Science, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Sympatric Seals, Satellite Tracking and Protected Areas: Habitat-Based Distribution Estimates for Conservation and Management - Matt I. D. Carter; Lars Boehme; Michelle A. Cronin; Callan D. Duck; W. James Grecian; Gordon D. Hastie; Mark Jessopp; Jason Matthiopoulos; Bernie J. McConnell; David L. Miller; Chris D. Morris; Simon E. W. Moss; et al. (Frontiers in Marine Science, 2022)
Marine predator populations are crucial to the structure and functioning of ecosystems. Like many predator taxa, pinnipeds face an increasingly complex array of natural and anthropogenic threats. Understanding the relationship between at-sea processes and trends in abundance at land-based monitoring sites requires robust estimates of at-sea distribution, often on multi-region scales. Such an understanding is critical for effective conservation management, but estimates are often limited in spatial extent by spatial coverage of animal-borne tracking data. Grey ( Halichoerus grypus ) and harbour seals ( Phoca vitulina ) are sympatric predators in North Atlantic shelf seas. The United Kingdom (UK) and Ireland represents an important population centre for both species, and Special Areas of Conservation (SACs) are designated for their monitoring and protection. Here we use an extensive high-resolution GPS tracking dataset, unprecedented in both size (114 grey and 239 harbour seals) and spatial coverage, to model habitat preference and generate at-sea distribution estimates for the entire UK and Ireland populations of both species. We found regional differences in environmental drivers of distribution for both species which likely relate to regional variation in diet and population trends. Moreover, we provide SAC-specific estimates of at-sea distribution for use in marine spatial planning, demonstrating that hotspots of at-sea density in UK and Ireland-wide maps cannot always be apportioned to the nearest SAC. We show that for grey seals, colonial capital breeders, there is a mismatch between SACs (where impacts are likely to be detected) and areas where impacts are most likely to occur (at sea). We highlight an urgent need for further research to elucidate the links between at-sea distribution during the foraging season and population trends observed in SACs. More generally, we highlight that the potential for such a disconnect needs to be considered when designating and managing protected sites, particularly for species that aggregate to breed and exhibit partial migration (e.g. grey seals), or spatial variation in migration strategies. We demonstrate the use of strategic tracking efforts to predict distribution across multiple regions, but caution that such efforts should be mindful of the potential for differences in species-environment relationships despite similar accessible habitats.

Flukebook: an open-source AI platform for cetacean photo identification - Drew Blount; Shane Gero; Jon Van Oast; Jason Parham; Colin Kingen; Ben Scheiner; Tanya Stere; Mark Fisher; Gianna Minton; Christin Khan; Violaine Dulau; Jaime Thompson; et al. (Mammalian Biology, 2022)
Determining which species are at greatest risk, where they are most vulnerable, and what are the trajectories of their communities and populations is critical for conservation and management. Globally distributed, wide-ranging whales and dolphins present a particular challenge in data collection because no single research team can record data over biologically meaningful areas. Flukebook.org is an open-source web platform that addresses these gaps by providing researchers with the latest computational tools. It integrates photo-identification algorithms with data management, sharing, and privacy infrastructure for whale and dolphin research, enabling the global collaborative study of these global species. With seven automatic identification algorithms trained for 15 different species, resulting in 37 species-specific identification pipelines, Flukebook is an extensible foundation that continually incorporates emerging AI techniques and applies them to cetacean photo identification through continued collaboration between computer vision researchers, software engineers, and biologists. With over 2.0 million photos of over 52,000 identified individual animals submitted by over 250 researchers, the platform enables a comprehensive understanding of cetacean populations, fostering international and cross-institutional collaboration while respecting data ownership and privacy. We outline the technology stack and architecture of Flukebook, its performance on real-world cetacean imagery, and its development as an example of scalable, extensible, and reusable open-source conservation software. Flukebook is a step change in our ability to conduct large-scale research on cetaceans across biologically meaningful geographic ranges, to rapidly iterate population assessments and abundance trajectories, and engage the public in actions to protect them.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Rise of the Machines: Best Practices and Experimental Evaluation of Computer-Assisted Dorsal Fin Image Matching Systems for Bottlenose Dolphins - Reny B. Tyson Moore; Kim W. Urian; Jason B. Allen; Carolyn Cush; Jason R. Parham; Drew Blount; Jason Holmberg; Jamie W. Thompson; Randall S. Wells (Frontiers in Marine Science, 2022)
Photographic-identification (photo-ID) of bottlenose dolphins using individually distinctive features on the dorsal fin is a well-established and useful tool for tracking individuals; however, this method can be labor-intensive, especially when dealing with large catalogs and/or infrequently surveyed populations. Computer vision algorithms have been developed that can find a fin in an image, characterize the features of the fin, and compare the fin to a catalog of known individuals to generate a ranking of potential matches based on dorsal fin similarity. We examined if and how researchers use computer vision systems in their photo-ID process and developed an experiment to evaluate the performance of the most commonly used, recently developed, systems to date using a long-term photo-ID database of known individuals curated by the Chicago Zoological Society’s Sarasota Dolphin Research Program. Survey results obtained for the “Rise of the machines – Application of automated systems for matching dolphin dorsal fins: current status and future directions” workshop held at the 2019 World Marine Mammal Conference indicated that most researchers still rely on manual methods for comparing unknown dorsal fin images to reference catalogs of known individuals. Experimental evaluation of the finFindR R application, as well as the CurvRank, CurvRank v2, and finFindR implementations in Flukebook suggest that high match rates can be achieved with these systems, with the highest match rates found when only good to excellent quality images of fins with average to high distinctiveness are included in the matching process: for the finFindR R application and the CurvRank and CurvRank v2 algorithms within Flukebook more than 98.92% of correct matches were in the top 50-ranked positions, and more than 91.94% of correct matches were returned in the first ranked position. Our results offer the first comprehensive examination into the performance and accuracy of computer vision algorithms designed to assist with the photo-ID process of bottlenose dolphins and can be used to build trust by researchers hesitant to use these systems. Based on our findings and discussions from the “Rise of the Machines” workshop we provide recommendations for best practices for using computer vision systems for dorsal fin photo-ID.

Genome-wide SNP analysis of three moose subspecies at the southern range limit in the contiguous United States - Jason A. Ferrante; Chase H. Smith; Laura M. Thompson; Margaret E. Hunter (Conservation Genetics, 2022)
Genome-wide evaluations of genetic diversity and population structure are important for informing management and conservation of trailing-edge populations. North American moose ( Alces alces ) are declining along portions of the southern edge of their range due to disease, species interactions, and marginal habitat, all of which may be exacerbated by climate change. We employed a genotyping by sequencing (GBS) approach in an effort to collect baseline information on the genetic variation of moose inhabiting the species’ southern range periphery in the contiguous United States. We identified 1920 single nucleotide polymorphisms (SNPs) from 155 moose representing three subspecies from five states: A. a. americana (New Hampshire), A. a. andersoni (Minnesota), and A. a. shirasi (Idaho, Montana, and Wyoming). Molecular analyses supported three geographically isolated clusters, congruent with currently recognized subspecies. Additionally, while moderately low genetic diversity was observed, there was little evidence of inbreeding. Results also indicated > 20% shared ancestry proportions between A. a. shirasi samples from northern Montana and A. a. andersoni samples from Minnesota, indicating a putative hybrid zone warranting further investigation. GBS has proven to be a simple and effective method for genome-wide SNP discovery in moose and provides robust data for informing herd management and conservation priorities. With increasing disease, predation, and climate related pressure on range edge moose populations in the United States, the use of SNP data to identify gene flow between subspecies may prove a powerful tool for moose management and recovery, particularly if hybrid moose are more able to adapt.

Bio-GO-SHIP: The Time Is Right to Establish Global Repeat Sections of Ocean Biology - Sophie Clayton; Harriet Alexander; Jason R. Graff; Nicole J. Poulton; Luke R. Thompson; Heather Benway; Emmanuel Boss; Adam Martiny (Frontiers in Marine Science, 2022)
In this article, we present Bio-GO-SHIP, a new ocean observing program that will incorporate sustained and consistent global biological ocean observations into the Global Ocean Ship-based Hydrographic Investigations Program (GO-SHIP). The goal of Bio-GO-SHIP is to produce systematic and consistent biological observations during global ocean repeat hydrographic surveys, with a particular focus on the planktonic ecosystem. Ocean plankton are an essential component of the earth climate system, form the base of the oceanic food web and thereby play an important role in influencing food security and contributing to the Blue Economy. Despite its importance, ocean biology is largely under-sampled in time and space compared to physical and chemical properties. This lack of information hampers our ability to understand the role of plankton in regulating biogeochemical processes and fueling higher trophic levels, now and in future ocean conditions. Traditionally, many of the methods used to quantify biological and ecosystem essential ocean variables (EOVs), measures that provide valuable information on the ecosystem, have been expensive and labor- and time-intensive, limiting their large-scale deployment. In the last two decades, new technologies have been developed and matured, making it possible to greatly expand our biological ocean observing capacity. These technologies, including cell imaging, bio-optical sensors and 'omic tools, can be combined to provide overlapping measurements of key biological and ecosystem EOVs. New developments in data management and open sharing can facilitate meaningful synthesis and integration with concurrent physical and chemical data. Here we outline how Bio-GO-SHIP leverages these technological advances to greatly expand our knowledge and understanding of the constituents and function of the global ocean plankton ecosystem.

Pulling Back the Blue Curtain: A Pelagic Monitoring Program for the Blue Belt - Jessica Jane Meeuwig; Christopher David Harburn Thompson; John Andrew Forrest; Hanna Jabour Christ; Tom Bech Letessier; Dirk Jason Meeuwig (Frontiers in Marine Science, 2021)
Ocean health is fundamental to human prosperity. However, fisheries exploitation, industrialization and climate change imperil our oceans. Marine protected areas (MPAs) have been established in coastal habitats since the 1970s and the ongoing monitoring of these MPAs has shown their general ecological and economic value. Demonstrable benefits can include biodiversity conservation, fisheries enhancement and climate resilience. Since the 2000s, large scale MPAs (LSMPAs) are increasingly established, with new parks including extensive areas of pelagic habitat. Seminal was the British Indian Ocean Territory (BIOT) MPA created in 2010. In 2016, the United Kingdom Government established the Blue Belt Programme to provide long-term protection of the marine environment across the United Kingdom Overseas Territories and LSMPAs have now been established or designated in a number of these territories. However, empirical data for the Blue Belt LSMPAs are needed to test their effectiveness in conserving pelagic species and to allow managers to monitor and assess the LSMPAs based on the best available evidence. This Perspective presents current advances in video-based monitoring of pelagic wildlife and provides examples of key ecological insights gained from their use that are relevant to LSMPA planning and management. We present a case study from the BIOT MPA and finally generalize with respect to key learning’s that will support planning and monitoring of LSMPAs within the Blue Belt Programme.

Microbiology of a NaCl stalactite ‘salticle’ in Triassic halite - Thomas P. Thompson; Stephen A. Kelly; Timofey Skvortsov; Gill Plunkett; Alastair Ruffell; John E. Hallsworth; Jason Hopps; Brendan F. Gilmore (Environmental Microbiology, 2021)
Summary Large regions of Earth's surface are underlain by salt deposits that evaporated from ancient oceans and are populated by extreme halophilic microbes. Some of these halophiles may have been preserved over geological timescales within hypersaline fluid inclusions, but ingresses of water and/or anthropogenic activities can lead to the formation of alternative habitats, including NaCl stalactites or other speleothems. While the microbiology of ancient evaporites has been well studied, the ecology of these recently formed structures is less‐well understood. Here, the microbiology of a NaCl stalactite (‘salticle’) in a Triassic halite mine is characterized. The specific aims were to determine the presence of fluid inclusions, determine the microbial structure of the salticle compared with a nearby brine‐pool and surficial soil, and characterize the ecophysiological capabilities of this unique ecosystem. The salticle contained fluid inclusions, and their microbiome was composed of Euryarchaetota, Proteobacteria, and Actinobacteria, with Haloarchaea in greater abundance than brine‐pool or soil microbiomes. The salticle metagenome exhibited a greater abundance of genes involved in osmoregulation, anaerobic respiration, UV resistance, oxidative stress, and stress‐protein synthesis relative to the soil microbiome. We discuss the potential astrobiological implications of salticles as enclosed salt‐saturated habitats that are protected from ionizing radiation and have a stable water activity.

Tolerance of wheat (Triticum aestivum) genotypes to root-lesion nematode (Pratylenchus thornei) in the subtropical grain region of eastern Australia - John P. Thompson; Jason G. Sheedy; Neil A. Robinson; Timothy G. Clewett (Euphytica, 2021)

Production and ecosystem structure in cold‐core vs. warm‐core eddies: Implications for the zooplankton isoscape and rock lobster larvae - Anya M. Waite; Eric Raes; Lynnath E. Beckley; Peter A. Thompson; David Griffin; Megan Saunders; Christin Säwström; Richard O'Rorke; Miao Wang; Jason P. Landrum; Andrew Jeffs (Limnology and Oceanography, 2019)
Anticyclonic (warm‐core) mesoscale eddies (WCEs) in the Eastern Indian Ocean carry higher surface chlorophyll signatures than cyclonic (cold‐core) eddies (CCEs). Paradoxically, WCEs host rock lobster larvae (phyllosomas) with lower lipid stores and protein reserves than phyllosomas in CCEs, suggesting a poorer nutritional status. We assess primary productivity and zooplankton isotopic data from eight eddies across four research voyages (2003–2011) to determine how this contradiction might occur. We find that WCEs and CCEs are equally productive per unit chlorophyll a , but depth‐integrated primary production (PP) is greater in eddies with shallower mixed layers (MLs), especially in CCEs. MLs tend to be shallower in CCEs than in WCEs because the pycnocline is closer to the surface. This, in combination with stronger stratification in CCE euphotic zones than those of WCEs, supports greater flagellate and dinoflagellate populations in CCEs. These phytoplankton provide high‐quality nutrition for zooplankton, which feed on average ~ 0.6 trophic level lower in CCEs with the shallowest MLs, accumulating high lipid stores. Conversely, WCEs have, on average, ~ 70 m deeper MLs than CCEs, and host a phytoplankton community with more diatoms. Diatoms provide lower quality food for zooplankton, and zooplankton lipid stores in WCEs decline with trophic level, and possibly, with time after initial (or seasonal) nutrient injection. As a result, phyllosomas in CCEs have higher energy and lipid content than those in warm‐core eddies. The resolution of the paradox, therefore, is that the higher surface chlorophyll signatures of WCEs are not representative of the nutritional value of the prey field of the phyllosoma. We also conclude that interannual variations of mixed layer depth occur at a regional scale, controlling PP.

Caffeine increases the velocity of rapid eye movements in unfatigued humans - Charlotte J. W. Connell; Benjamin Thompson; Jason Turuwhenua; Robert F. Hess; Nicholas Gant (Psychopharmacology, 2017)

Consequences of altered temperature regimes for emerging freshwater invertebrates - Paula Sardiña; John Beardall; Jason Beringer; Mike Grace; Ross M. Thompson (Aquatic Sciences, 2017)

Effects of life‐history requirements on the distribution of a threatened reptile - Denise M. Thompson; Day B. Ligon; Jason C. Patton; Monica Papeş (Conservation Biology, 2017)
Survival and reproduction are the two primary life‐history traits essential for species’ persistence; however, the environmental conditions that support each of these traits may not be the same. Despite this, reproductive requirements are seldom considered when estimating species’ potential distributions. We sought to examine potentially limiting environmental factors influencing the distribution of an oviparous reptile of conservation concern with respect to the species’ survival and reproduction and to assess the implications of the species’ predicted climatic constraints on current conservation practices. We used ecological niche modeling to predict the probability of environmental suitability for the alligator snapping turtle (Macrochelys temminckii). We built an annual climate model to examine survival and a nesting climate model to examine reproduction. We combined incubation temperature requirements, products of modeled soil temperature data, and our estimated distributions to determine whether embryonic development constrained the northern distribution of the species. Low annual precipitation constrained the western distribution of alligator snapping turtles, whereas the northern distribution was constrained by thermal requirements during embryonic development. Only a portion of the geographic range predicted to have a high probability of suitability for alligator snapping turtle survival was estimated to be capable of supporting successful embryonic development. Historic occurrence records suggest adult alligator snapping turtles can survive in regions with colder climes than those associated with consistent and successful production of offspring. Estimated egg‐incubation requirements indicated that current reintroductions at the northern edge of the species’ range are within reproductively viable environmental conditions. Our results highlight the importance of considering survival and reproduction when estimating species’ ecological niches, implicating conservation plans, and benefits of incorporating physiological data when evaluating species’ distributions.

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

How robust is the pre-1931 National Climatic Data Center—climate divisional dataset? Examples from Georgia and Louisiana - Jason Allard; Clint Thompson; Barry D. Keim (Theoretical and Applied Climatology, 2015)

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

The importance of developing modeling frameworks to inform conservation decisions: a response to Lonergan - Jason Matthiopoulos; Sophie Smout; Marjolaine Caillat; Line Cordes; Beth Mackey; Paul Thompson (Oecologia, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genetic analysis of quantitative phenotypes in AD and MCI: imaging, cognition and biomarkers - Li Shen; Paul M. Thompson; Steven G. Potkin; Lars Bertram; Lindsay A. Farrer; Tatiana M. Foroud; Robert C. Green; Xiaolan Hu; Matthew J. Huentelman; Sungeun Kim; John S. K. Kauwe; Qingqin Li; et al. (Brain Imaging and Behavior, 2014)

Best Practices for the Development, Scale-up, and Post-approval Change Control of IR and MR Dosage Forms in the Current Quality-by-Design Paradigm - Glenn A. Van Buskirk; Satish Asotra; Christopher Balducci; Prabir Basu; Gerald DiDonato; Angelica Dorantes; W. Mark Eickhoff; Tapash Ghosh; Mario A. González; Theresa Henry; Matthew Howard; Jason Kamm; et al. (AAPS PharmSciTech, 2014)

State-space modelling reveals proximate causes of harbour seal population declines - Jason Matthiopoulos; Line Cordes; Beth Mackey; David Thompson; Callan Duck; Sophie Smout; Marjolaine Caillat; Paul Thompson (Oecologia, 2014)

Moving beyond methods: the need for a diverse programme in climate change research - Ross M. Thompson; John Beardall; Jason Beringer; Mike Grace; Paula Sardina (Ecology Letters, 2014)
Understanding effects of climate change on ecosystems will require a diverse range of approaches. We proposed using downscaled climate models to generate realistic weather scenarios as experimental treatments. Kreyling et al . propose a gradient approach to determine the shape of response functions. These approaches are different, but highly complementary.

Genome-wide association identifies genetic variants associated with lentiform nucleus volume in N = 1345 young and elderly subjects - Derrek P. Hibar; Jason L. Stein; April B. Ryles; Omid Kohannim; Neda Jahanshad; Sarah E. Medland; Narelle K. Hansell; Katie L. McMahon; Greig I. de Zubicaray; Grant W. Montgomery; Nicholas G. Martin; Margaret J. Wright; et al. (Brain Imaging and Behavior, 2013)

Means and extremes: building variability into community‐level climate change experiments - Ross M. Thompson; John Beardall; Jason Beringer; Mike Grace; Paula Sardina (Ecology Letters, 2013)
Experimental studies assessing climatic effects on ecological communities have typically applied static warming treatments. Although these studies have been informative, they have usually failed to incorporate either current or predicted future, patterns of variability. Future climates are likely to include extreme events which have greater impacts on ecological systems than changes in means alone. Here, we review the studies which have used experiments to assess impacts of temperature on marine, freshwater and terrestrial communities, and classify them into a set of ‘generations’ based on how they incorporate variability. The majority of studies have failed to incorporate extreme events. In terrestrial ecosystems in particular, experimental treatments have reduced temperature variability, when most climate models predict increased variability. Marine studies have tended to not concentrate on changes in variability, likely in part because the thermal mass of oceans will moderate variation. In freshwaters, climate change experiments have a much shorter history than in the other ecosystems, and have tended to take a relatively simple approach. We propose a new ‘generation’ of climate change experiments using down‐scaled climate models which incorporate predicted changes in climatic variability, and describe a process for generating data which can be applied as experimental climate change treatments.

Geographic divergence in a species‐rich symbiosis: interactions between Monterey pines and ectomycorrhizal fungi - Jason D. Hoeksema; Jesus Vargas Hernandez; Deborah L. Rogers; Luciana Luna Mendoza; John N. Thompson (Ecology, 2012)
A key problem in evolutionary biology is to understand how multispecific networks are reshaped by evolutionary and coevolutionary processes as they spread across contrasting environments. To address this problem, we need studies that explicitly evaluate the multispecific guild structure of coevolutionary processes and some of their key outcomes such as local adaptation. We evaluated geographic variation in interactions between most extant native populations of Monterey pine ( Pinus radiata ) and the associated resistant‐propagule community (RPC) of ectomycorrhizal (EM) fungi, using a reciprocal cross‐inoculation experiment with all factorial combinations of plant genotypes and soils with fungal guilds from each population. Our results suggest that the pine populations have diverged in community composition of their RPC fungi, and have also diverged genetically in several traits related to interactions of seedlings with particular EM fungi, growth, and biomass allocation. Patterns of genetic variation among pine populations for compatibility with EM fungi differed for the three dominant species of EM fungi, suggesting that Monterey pines can evolve differently in their compatibility with different symbiont species.

Hybridisation of Australian chickpea cultivars with wild Cicer spp. increases resistance to root-lesion nematodes (Pratylenchus thornei and P. neglectus) - John P. Thompson; Roslyn A. Reen; Timothy G. Clewett; Jason G. Sheedy; Alison M. Kelly; Beverley J. Gogel; Edward J. Knights (Australasian Plant Pathology, 2011)

Genes in the insulin and insulin-like growth factor pathway and odds of metachronous colorectal neoplasia - Elizabeth C. LeRoy; Jason H. Moore; Chengcheng Hu; María Elena Martínez; Peter Lance; David Duggan; Patricia A. Thompson (Human Genetics, 2011)

Effects of Central Airway Shunting on the Mechanical Impedance of the Mouse Lung - Benjamin L. Schwartz; Ron C. Anafi; Minara Aliyeva; John A. Thompson-Figueroa; Gilman B. Allen; Lennart K. A. Lundblad; Jason H. T. Bates (Annals of Biomedical Engineering, 2011)

Range‐wide distribution of genetic diversity in the North American tree Juglans cinerea : a product of range shifts, not ecological marginality or recent population decline - SEAN M. HOBAN; DANIEL S. BORKOWSKI; SUNSHINE L. BROSI; TIM S. McCLEARY; LAURA M. THOMPSON; JASON S. McLACHLAN; MARIE A. PEREIRA; SCOTT E. SCHLARBAUM; JEANNE ROMERO‐SEVERSON (Molecular Ecology, 2010)
The spatial distribution of genetic diversity is a product of recent and historical ecological processes, as well as anthropogenic activities. A current challenge in population and conservation genetics is to disentangle the relative effects of these processes, as a first step in predicting population response to future environmental change. In this investigation, we compare the influence of contemporary population decline, contemporary ecological marginality and postglacial range shifts. Using classical model comparison procedures and Bayesian methods, we have identified postglacial range shift as the clear determinant of genetic diversity, differentiation and bottlenecks in 29 populations of butternut, Juglans cinerea L., a North American outcrossing forest tree. Although butternut has experienced dramatic 20th century decline because of an introduced fungal pathogen, our analysis indicates that recent population decline has had less genetic impact than postglacial recolonization history. Location within the range edge vs. the range core also failed to account for the observed patterns of diversity and differentiation. Our results suggest that the genetic impact of large‐scale recent population losses in forest trees should be considered in the light of Pleistocene‐era large‐scale range shifts that may have had long‐term genetic consequences. The data also suggest that the population dynamics and life history of wind‐pollinated forest trees may provide a buffer against steep population declines of short duration, a result having important implications for habitat management efforts, ex situ conservation sampling and population viability analysis.

Linking fish population dynamics to habitat conditions: insights from the application of a process-oriented approach to several Great Lakes species - Daniel Hayes; Michael Jones; Nigel Lester; Cindy Chu; Susan Doka; John Netto; Jason Stockwell; Bradley Thompson; Charles K. Minns; Brian Shuter; Nicholas Collins (Reviews in Fish Biology and Fisheries, 2009)

C2/c pyroxene phenocrysts from three potassic series in the Neogene alkaline volcanics, NE Turkey: their crystal chemistry with petrogenetic significance as an indicator of P–T conditions - Faruk Aydin; Richard M. Thompson; Orhan Karsli; Hinako Uchida; Jason B. Burt; Robert T. Downs (Contributions to Mineralogy and Petrology, 2009)

Thoracic Gas Volume Measurements in Paralyzed Mice - Lennart K. A. Lundblad; John Thompson-Figueroa; Timothy Leclair; Charles G. Irvin; Jason H. T. Bates (Annals of Biomedical Engineering, 2004)

What We Know -- and Don't Know -- about Water Quality at Stream Crossings - Steven E. Taylor; Robert B. Rummer; Kyung H. Yoo; Richard A. Welch; Jason D. Thompson (Journal of Forestry, 1999)
Forest road stream crossings, including fords, culverts, and bridges, are primary contributors of sediment to forest streams. Information on the water quality impacts from each type of crossing is limited, but the available literature indicates that significant amounts of sediment are produced during installation of fords and culverts; construction and use of temporary bridges have the least impact on water quality. This review of our current state of knowledge on the water quality impacts from crossings shows that we need date for a wide variety of steam sizes, soil types, terrain, and climatological conditions so that policymakers can develop scientifically sound best management practices.